Study of the prevalence of malaria parasite in migrant workers using rapid diagnostic test (RDTs) in Sebha, Libya. (Journal of Medical Sciences, 2022)
Malaria is a parasitic infection caused by a parasite of the Plasmodiidae family, Plasmodium that infects humans and is transmitted by female Anopheles mosquitoes. 229 million cases of malaria were recorded worldwide in 2019 and caused 409,000 deaths. Africa bears the brunt of this Infections Especially in sub-Saharan Africa, imported malaria cases among expatriates coming from endemic areas to malaria-free countries are a risk factor for these countries, so testing RDTs for the detection of the parasite in this category has been used as one of the prevention and control programs for the disease that requires intensification by Several parties related to disease control. This study was conducted during February and March of the year 2020 in the health care center in Sebha city. The study population included 135 people (males and females), their ages ranged from 15-67 years, who were subjected to a standardized questionnaire and examination of venous blood samples using the RDTs test.The results of our study showed that the prevalence rate of 14.8% (20) malaria cases out of the total number of cases, the age group 15-24 males had the highest incidence of Plasmodium falciparum malaria, and it was found through our study that there is a significant correlation between infection rate and educational level P=0.00 This is due to the lack of knowledge of ways to prevent the disease, and there was a significant correlation between infection rate and housing, P=0.02, which confirms the presence of a high prevalence of the vector in the affected villages. The aim of the study is to determine the extent of the malaria parasite prevalence and associated risk factors among expatriate workers in the city of Sebha using the Rapid Diagnostic Test (RDTs).